Equity financing in nigeria - Mbatomon, Rose Ako (Nigeria, 1997)
The capital market has emerged as a major area of economic advancement especially in developing countries, as such this book is written to provide a unique, pioneering and authentic theory and evidence of the Nigeria capital market.
143-153, includes appendix
nmn, 04/08/16
Loan
Keywords: Capital market; Equity financing; Finance; Nigeria